-y-2(2y-1)=5(1-y)

Simple and best practice solution for -y-2(2y-1)=5(1-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -y-2(2y-1)=5(1-y) equation:


Simplifying
-1y + -2(2y + -1) = 5(1 + -1y)

Reorder the terms:
-1y + -2(-1 + 2y) = 5(1 + -1y)
-1y + (-1 * -2 + 2y * -2) = 5(1 + -1y)
-1y + (2 + -4y) = 5(1 + -1y)

Reorder the terms:
2 + -1y + -4y = 5(1 + -1y)

Combine like terms: -1y + -4y = -5y
2 + -5y = 5(1 + -1y)
2 + -5y = (1 * 5 + -1y * 5)
2 + -5y = (5 + -5y)

Add '5y' to each side of the equation.
2 + -5y + 5y = 5 + -5y + 5y

Combine like terms: -5y + 5y = 0
2 + 0 = 5 + -5y + 5y
2 = 5 + -5y + 5y

Combine like terms: -5y + 5y = 0
2 = 5 + 0
2 = 5

Solving
2 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8=10-2n | | 3x^2-5=54 | | 8=10-2 | | 8x-9y+73= | | 4(x-1)-x=23 | | Y=-2x^2+4x+8 | | x+3.5x=9.90 | | -6k-7=-(6k-7) | | 10=6+2w | | 30x^3-24x^2-15x+12=0 | | 2x-84=7x-4 | | 8(p-3)=8(1+p) | | 3g-5=1 | | x-14+2x=16 | | (2y-1)(y-2)=6 | | 9x+84=12 | | 5y+13=2y+22 | | 6x-4-4x=2x-4 | | 4x+15=24 | | 24-64n=-8(-3+8n) | | 7x-13=42 | | 4x^2-17x-15=30 | | -85=5(2n-3) | | 3x+10=2x-x+18 | | 11x+25=78 | | -2(z-3)-4=18 | | -2-(12x+8)+17=3+x-(13x-4) | | -12z-29=5(z+6)-195 | | 5(v-8)-2=5v+29 | | a(t)=t^2-6t+24 | | 1.6+0.2x=0.4x-3.2 | | 60x^2+300x=0 |

Equations solver categories